The Relationship Between Smartphone Usage Duration and Cognitive Development in Children Aged 4-6 Years - Titis Sensussiana; Mutiara Dewi Listyanawati; Noerma Shovie Rizqiea; Endang Zulaicha Susilaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2026)
Background: Prolonged and continuous smartphone use, even from infancy, can have adverse effects on personality and intellectual development.Objective: The purpose of this study to determine the relationship between the duration of smartphone use and the cognitive development of children aged 4–6 years.Methods: This research method uses quantitative research method. The study population consists of 74 students, and sampling was conducted using total sampling.Results: This research method used quantitative methods. The population was 74 students and the sampling method was total sampling. The data collection questionnaire used a standardized KPSP, while for the duration of gadget use, a checklist was used. The results of this study showed a significant relationship between the duration of smartphone use and the cognitive abilities of children aged 4-6 years at TK Negeri 1 Pembina Jebres, as proven by statistical tests showing a p-value <0.000.Conclusion: Parents should monitor their children when they use smartphones and ensure they observe the set time limits.